Research communities and open collaboration: the example of the Digital Classicist wiki - Simon Mahony (Digital Medievalist, 2011)
The so-called Web 2.0 technologies bring with them new opportunities and new challenges in the field of scholarship. With social software we have a new set of tools with innovative possibilities and it is up to the community of practitioners in the area of the intersection between scholarship and technology to make effective use of them. This paper is part of the author's continuing research into the use of social software (blogs and wikis amongst others) as tools for education (meaning teaching and learning) and research. The primary interest is in how these new tools might facilitate cooperative learning and cooperative research, and help to build communities both of learning and of practice. Put simply, how can they be used to encourage and facilitate people working together, to be a medium for open collaboration; why is this necessary; and what perceived problems need to be addressed to make this happen?